Analisis Quality of Service (QoS) Jaringan Internet Berbasis Wireless Local Area Network pada Layanan Indihome - Robby Faishal Bari; Arip Solehudin; Nono Heryana (Jurnal Ilmiah Wahana Pendidikan, 2022)
Quality of Service (QoS) is a method used in the network that functions to provide more optimal services and can ensure that users can use the network in maximum performance. One method that can be used to stabilize internet speed is bandwidth management, at the Tepi Kota coffee shop there are often problems with the wlan internet network, causing inconvenience to internet users at the shop. This problem is caused by the absence of bandwidth management so that the bandwidth received by clients is not evenly distributed. Therefore, bandwidth management is needed at the Tepi Kota coffee shop so that clients or visitors who stop at the shop can use the WLAN internet network comfortably without any problems. The method used in bandwidth management is the PCQ (Per Connection Queue) method, the PCQ method is a simple method where PCQ works in an algorithm that can divide evenly on active clients. This method was chosen because it is considered effective enough to be applied in public places. The research methodology used in this study is Action Research (AR) with 5 interrelated stages, namely Diagnosis, Action Plan, Action, Evaluation, and Learning. The results obtained in testing the Quality of Service (QoS) parameters in 3 phases at the Tepi Kota coffee shop are better after bandwidth management using the PCQ method. These results are in accordance with the TIPHON standard, with the average results obtained in testing the initial packet loss parameter of 5.5% to 1.37%, the initial delay parameter of 50.5ms to 16.3ms, and the initial jitter parameter of 50.5ms to 15 ,6ms Keywords: Action Research (AR), Bandwidth Management, Per Connection Queue (PCQ), Quality of Service (QoS).